Pemberdayaan PKK Kelurahan Sukomulyo di Era Pandemi COVID-19 dengan Inovasi Masker Face Shield - Trias Madanika Kusumaningrum; Dewie Tri Wijayati; Hujjatullah Fazlurrahman; Hafid Kholidi Hadi; Achmad Kautsar (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
In early 2020, almost all countries in the world, including Indonesia, experienced the impact of the COVID-19 virus pandemic. The people of Sukomulyo Lamongan Village are among those affected economically as a result of this pandemic. To overcome this problem, we have the initiative to provide training on making face shield masks to stop the spread of the COVID-19 virus. The mask making training is expected to be able to increase knowledge and increase the income of program at village level to educate women on various aspects of family welfare or woman in PKK (Pendidikan Kesejahteraan Keluarga). The purpose of this community service implementation is to reduce the impact of the COVID-19 pandemic, and to create independence woman in PKK by learning to produce face shield masks. The method we do is by socializing about COVID-19, healthy living patterns during the pandemic, and training in making face shield masks. The results of this activity, which can be seen from the results of the questionnaire, show that 70% feel moved to implement the 5M and MIO movements, and 76% of participants plan to practice making their own face shield masks and will be sold. It can be concluded that this activity provides new experiences for PKK mothers in the Sukomulyo village about the importance of maintaining health during a pandemic, and making face shield masks.DOI: https://doi.org/10.26905/abdimas.v6i1.4887